فلسفة التاريخ النقدية عند شارل مونتسكيو (1689-1755م) (Comprehensive Journal of Science, 2025)
The study aimed to identify the critical Philosophy of history of Charles Montesquieu, one of the Philosophers of the Enlightenment in Europe, and the first to call for the application of the system of separation of powers, his studies inspired the US Constitution, the Declaration of the Rights of Man, and the French Constitution after the French Revolution.The study used the historical approach to study philosophy in its historical context. It also followed the descriptive approach to describe and analyze philosophical ideas in a scientific manner. The study reached several main results, including: power should be divided into three governmental branches: legislative, executive, and judicial prevents the concentration of power in the hands of a single person, and the law must be applied to everyone without discrimination. The study recommends further research on Enlightenment philosophers.